Approximation of Conjugate of Functions belonging to Lip (alpha) Class and Weighted Class (L(r), xi(t)) by Product Means of Conjugate Series of Fourier Series (European Journal of Pure and Applied Mathematics, 2011)
In this paper, two quite new theorems on degree of approximation of conjugate of functionsÂ Â  fLip Î± class and fW(Lr,Î¾(t) class using (E,1)(C,1) product summability means of conjugate series of Fourier series have been established.